A new Paleoproterozoic tectonic history of the eastern Capricorn Orogen, Western Australia, revealed by U–Pb zircon dating of micro-tuffs - Sheppard, Steve; Fletcher, I.; Rasmussen, Birger; Zi, Jianwei; Muhling, Janet; Occhipinti, S.; Wingate, Michael; Johnson, S. (Elsevier BV, 2016)
The Earaheedy Basin is one of several Paleoproterozoic siliciclastic basins in the eastern part of the Capricorn Orogen in Western Australia. In the absence of an adequate chronostratigraphic framework, multiple conflicting models have been proposed for the tectonic history of the basin. We present in situ SHRIMP U–Pb zircon dates of 1971 ± 11 Ma, 1954 ± 5 Ma and 1949 ± 10 Ma from three thin tuff horizons (“micro-tuffs”) in the Yelma Formation at the base of the basin succession. These micro-tuffs are only slightly younger than the 1990 ± 6 Ma Imbin porphyry, which has been interpreted as a basement inlier. Our new dates, combined with field mapping, suggest that the Imbin porphyry is a volcanic–subvolcanic complex within the basin. Micro-tuffs in the Yelma Formation are more than 50 m.y. older than c. 1890 Ma micro-tuffs within the overlying Frere Formation. Deposition of the Yelma Formation was coeval with continent–continent collision farther west in the Orogen marked by the 2005–1950 Ma Glenburgh Orogeny, and the formation is possibly correlative with peripheral foreland deposits of the Padbury Group. The Frere Formation was deposited in shallow marine conditions within an intracratonic basin about 60 m.y. after the Glenburgh Orogeny. The Frere Formation is unconformably or disconformably overlain by the Miningarra Group, the youngest unit of which is the Mulgarra Sandstone. This sandstone was deposited after c. 1865 Ma, and derived either from exposed Frere Formation or from a now-buried source within the Capricorn Orogen that was uplifted by inception of the 1820–1770 Ma Capricorn Orogeny. Therefore, the Earaheedy Basin comprises at least three distinct, unconformity-bound successions deposited in contrasting tectonic settings.